Being Alive: Literature in War (About "Los pichiciegos" by Rodolfo Fogwill) - Rodríguez, Fermín A. (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
In the final decades of twentieth century new subjectivities and life forms surfacing beyond the traditional ways of imaginary identification of the individual with the nation have became the core of different political, aesthetic and cultural processes in Latin America, according to a cultural configuration dominated by the temporality of the crisis and the emptying of the meaning of the national. By introducing new ways of organization of the sensible, Rodolfo Fogwill’s novel Los pichiciegos (1983) represents a rupture with the traditional territorialization of the State. Fogwill's novel is a picaresque of deserters from the Guerra de Malvinas abandoned in a state of the exception that predicts in many ways the cynicism of neoliberal policies as well as new forms of community in Argentina during the 90’s.
Keywords: Literature and war; Neoliberalism; Biopolitics; Community; Fogwill